TINGKAT KESUKAAN DAN NILAI GIZI COOKIES DENGAN PENAMBAHAN TEPUNG DAUN KATUK DAN TEPUNG DAUN KELOR UNTUK IBU MENYUSUI - Thobagus Muhammad Nu'man; Asrul Bahar (Faculty of Agricultural Technology, University of Jember, 2021)
Katuk leaves [Sauropus androgynus (L.) Merr] and moringa leaves (Moringa oleifera Lam.) are plants that can be used as galactagogues. Galactagogues compounds in both can stimulate the hormones prolactin and oxytocin, thereby increasing milk production. Katuk leaves and moringa leaves have a natural taste that is not favoured so that processing and formulation of other ingredients are needed to make the two ingredients more preferable. With an average growth from 2016-2020 of 4.250%, cookies can be a medium to help meet human needs. This study purposed to determine the level of preference and nutritional value of cookies with the addition of katuk leaves and moringa leaves as a snack for nursing mothers. This study used a factorial research design with 2 factors, namely 3 levels of katuk leaf flour (5 g, 10 g, 15 g) and 2 levels of moringa leaf flour (5 g, 10 g). The hedonic test data were processed using the Friedman test and further test with the Wilcoxon signed-rank test. Calculations used to test the effectiveness to determine the selected formula showed that the F4 treatment (5 g katuk leaf flour: 10 g moringa leaf flour) had the highest effectiveness value of 0.95. The results of the chemical test on the F4 treatment had a water content of 1.02%, carbohydrates 76.88%, protein 12.05%, fat 7.85%, and energy contributions of 423.50 kcal per 100 g, and 105.87 kcal per dose serving (30 g). Keywords: breastfeeding mothers, cookies, katuk leaves, moringa leaves